Property Issues Relating to Deep-Seabed Mining in the Light of the United Convention on the Sea of 1982 - Hennicke, Larisa (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The study aims at the evaluation of the right to property in the context of the deep-seabed mining. The author present deep-seabed mining in the light of the United Convention on the Sea of 1982 focusing on the lack of knowledge about the oceans and the lack of regulations regarding the protection and enhancement of the oceans.